Dried grape pomace influenced fatty acids composition of Longissimus dorsi muscle and plasma polyphenols spectrum in finishing pigs - HABEANU, MIHAELA; LEFTER, NICOLETA A; ROPOTA, MARIANA; CHEDEA, VERONICA S; GHEORGHE, ANCA; TOMA, SMARANDA M; CIURESCU, GEORGETA; DRAGOMIR, CÃTÃLIN (The Indian Journal of Animal Sciences, 2015)
The experiment assessed the fatty acids (FA) composition of Longissimus dorsi (LD) muscle and plasma polyphenols spectrumin finishing hybrid Topigs fed diets containing dried grape pomace (DGP). The trial was conducted on 24 hybrids Topigs, 75.54±5.55 kg, randomly assigned for 28-d experimental period, to 2 groups, viz. a control (C diet), and an experimental (E diet) with the additional inclusion of 50 g DGP / kg diet. The FA composition wasanalysed by gas chromatography and all the spectra were recorded by spectrophotometry. The results of the study prove that the DGP, by its high content of polyunsaturated fatty acids (PUFA, over 60% of total FAME) and by the active principles such as polyphenols (lmax =273 nm), is a valuable feed which improvedfatty acids composition of LD muscle. In addition, the polyphenols from GP changed in plasma, maximum changes from 273 nm to 279 nm. These properties were reflectedin a positive influence on muscle n-3 FA composition (>1.27 times in DGP group than control group, p=0.02), particularly alpha-linolenicFA (>1.35 times) and eicosapentaenoic FA (>1.30 times than C diet), known for their health benefits.